Diversitas Budaya Suku Batak di Sumatera Utara : Analisis Literatur Sistematis terhadap Bahasa, Tradisi, dan Sistem Sosial - Marzuti Isra; Nisa Widia Agustira; Ahmad Alifsyah Harahap; Zahrotul Hayati Sibarani; Muhammad Nabil Syahputra Gultom; Abdi Akbar Tanjung (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines the cultural diversity of the Batak people in North Sumatra through a systematic literature review of three core pillars: language, traditions, and social systems. Findings reveal significant inter-sub-ethnic variations (e.g., Toba, Karo, Simalungun), including linguistic diversity (V-S-O structures in Toba vs. complex affixation in Karo), distinct rituals (such as Saur Matua and Manulangi Natuatua), and kinship systems rooted in the Dalihan Na Tolu philosophy. Amid positive dynamics like digitalization of traditional arts (Tortor Martonun) and gender transformations, Batak culture faces critical threats: symbolic desacralization (commodification of ulos textiles), kinship disintegration (atomization of Dalihan Na Tolu due to urbanization), and erosion of transcendental knowledge (extinction of Hata Andung rituals). The study recommends a community-based participatory research (CBPR) preservation model, integrating local content curricula and geographical indication certification. A key limitation is the literature bias toward the Toba sub-group, necessitating urgent comparative studies across sub-ethnicities and analysis of digital media’s impact on cultural transmission.